1997
DOI: 10.2307/2445823
|View full text |Cite
|
Sign up to set email alerts
|

Is Ginkgo biloba (Ginkgoaceae) really an oviparous plant?

Abstract: Germination of Ginkgo biloba seeds with intact and removed sarcotesta was compared to test the role of the seed coat in germination biology. The presence of an intact sarcotesta significantly reduced total germination percentage when compared to seeds with the sarcotesta removed. Some seeds were also cold stratified. This treatment was not necessary for germination, but it did improve total germination percentage. The seeds were collected during the period of natural abscission. Contrary to the accepted litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In the majority of gymnosperms, the female gametophyte is poorly developed at the time of pollen receipt, and often completely lacks egg nuclei (Sarvas 1962; Owens et al 1981; Haig 1992). A considerable delay can exist between pollen receipt and fertilization, during which time a significant amount of resources can be allocated to pollinated gametophytes, irrespective of pollen quality (Brough and Taylor 1940; Favre‐Duchartre 1958, but see Sarvas 1962; Lill 1976; Haig 1992; Holt and Rothwell 1997). In many other species, growth occurs both before and after fertilization; however, pollinated but unfertilized ovules still develop into full‐sized but empty seeds (Haig 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of gymnosperms, the female gametophyte is poorly developed at the time of pollen receipt, and often completely lacks egg nuclei (Sarvas 1962; Owens et al 1981; Haig 1992). A considerable delay can exist between pollen receipt and fertilization, during which time a significant amount of resources can be allocated to pollinated gametophytes, irrespective of pollen quality (Brough and Taylor 1940; Favre‐Duchartre 1958, but see Sarvas 1962; Lill 1976; Haig 1992; Holt and Rothwell 1997). In many other species, growth occurs both before and after fertilization; however, pollinated but unfertilized ovules still develop into full‐sized but empty seeds (Haig 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Cox et al , 2003). In general, sarcotesta function requires further investigation; for example, it has been suggested that the sarcotesta of Gingko biloba might function primarily as a germination‐delaying mechanism facilitating winter dormancy (Holt & Rothwell, 1997). However, frugivory has also been suggested as essential for Gingko germination and various scenarios for Gingko /vertebrate co‐evolution (including several that implicate non‐avian dinosaurs) have been proposed (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…One of the spermatozoids fertilizes the egg cell while the ovule remains on the tree. [ 19 33 34 ] Developing ovules are green-colored till maturity in the autumn, when they turn yellow due to changing temperatures and fall from the tree 1 month after fertilization occurs. Embryo maturation completes in 6-8 weeks after seeds fall, and the foul odor from the fruits indicates that they are mature.…”
Section: Biologymentioning
confidence: 99%
“…[ 35 36 ] Mature ginkgo seeds are large, comprising an embryo embedded in the female gametophyte tissue and surrounded by a thick seed coat that has soft, fleshy sarcotesta, a hard stony middle layer, and a thin membranous inner layer. [ 34 ] Several authors have suggested many different animals as seed dispersal agents in geological history and in modern times, and many mammals have been observed as dispersal agents. [ 37 ] The seeds fall from the tree in a state of dormancy before the embryo has developed, and when cleaned and placed in a warm greenhouse after dispersal, the embryo grows to full size and germinates within 8-10 weeks.…”
Section: Biologymentioning
confidence: 99%